The comparison of the effectiveness of acceptance, commitment, and reality therapy on life satisfaction and self-care behaviors of the elderly with type II diabetes - Behzadi, Soudabeh; Tajeri, Biuok; Sodagar, Sheida; Shariati, Zahra (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to compare the effectiveness of acceptance, commitment, and reality therapy on life satisfaction and self-care behaviors of the elderly with type II diabetes. Methods: The method of this research was a quasi-experimental with a pretest-posttest design and follow-up period with two experimental and one control groups. The statistical population included all elderly diabetic patients (type II) referred to technical clinics for diabetic patients in Shiraz in 2020-2021. In this population, 60 people were selected by purposive sampling along with screening. And based on Morgan table, they were assigned into differen groups (20 participants in experimental group 1 and 20 in experimental group 2, and 20 in the control group). All three groups were first using the Satisfaction With Life Scale (Diener, et al., 1985) and the Johnson Self-Care Ability Questionnaire (2008). Both experimental groups received eight sessions of 90-minute intervention based on Haye’s acceptance and commitment therapy (2004) and reality therapy based on William Glasser’s (2000) theory, and the control group did not receive any intervention. The data were analyzed using repeated measures of variance. Result: The results indicated the effect of treatment intervention based on acceptance and commitment and reality therapy on life satisfaction scores (F = 4.65, P = 0.013) and self-care behaviors (F = 10.57, P = 0.001). And this effect was stable in the follow-up stage. Conclusion: According to the results of the study, it can be concluded that therapists can use the treatment based on acceptance, commitment, and reality therapy as the preferred therapies in the intervention of the elderly with type II diabetes.